2000
DOI: 10.1053/eupc.1999.0093
|View full text |Cite
|
Sign up to set email alerts
|

Early cardioversion of atrial fibrillation and atrial flutter guided by transoesophageal echocardiography. A single centre 8·5-year experience

Abstract: Transoesophageal echocardiography-guided early cardioversion in concert with short-term anticoagulation is safe. This approach permits abbreviation of the overall duration of atrial fibrillation and has a better impact on the maintenance of sinus rhythm for patients in whom the duration of atrial fibrillation is < 4 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…These findings suggest that hs-CRP levels are associated with AF recurrence. In our study, the success rate of CV and the rate of AF recurrence at 12 months were similar to previous data [19,20]. …”
Section: Discussionsupporting
confidence: 80%
“…These findings suggest that hs-CRP levels are associated with AF recurrence. In our study, the success rate of CV and the rate of AF recurrence at 12 months were similar to previous data [19,20]. …”
Section: Discussionsupporting
confidence: 80%
“…Stoddard 28 demonstrated that patients receiving anticoagulation following conventional treatment had a higher prevalence of both thorombus and SEC in LA compared with patients who underwent cardioversion early. Corrado 30 demonstrated that patients with and <4 weeks duration of AF had a significantly better immediate success rate of CV than those with longer duration of AF (96.9% versus 85%); improved outcome was maintained at 1 month. This study helped show that not only did patients tolerate abbreviated anticoagulation, but also earlier termination of AF had a positive effect on immediate success and maintenance of sinus rhythm.…”
Section: Reviews Continuedmentioning
confidence: 98%
“…The flowchart of the systematic review is depicted in Figure . Of the 8,468 articles screened, 17 articles were selected for the final analyses . The initial and follow‐up data of the articles included in the final analyses are listed in Table and in Table , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Only two of the 17 studies included in the final review noted inclusion of subjects with rheumatic disease . Corrado et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation